Monetary Union Accession and the Severity of Potential Asymmetric Shocks - the Case of Lithuania and Poland - Kurach, Radosław; Stelmach, Jerzy (Ekonomika, 2008)
Monetary union accession generates benefits and costs for the entering countries. According to the seminal paper by Mundell (1961), the possible costs are usually associated with the asymmetric shocks that might take place. Under the currency union regime, these asymmetric shocks can be no longer neutralized by the countryspecific monetary policy tools, hence the flexibility of the economy is desirable.In this article, we employ the measure of business cycles correlation proposed by Artis and Zhang (1995) as well as labor market statistics to examine how easy the economies of Lithuania and Poland can adjust to asymmetric shocks in comparison to some other EU countries. Discussing the empirical results, we propose recommendations for economic policy that might help to fulfil the conditions of the Optimum Currency Area.